TEACHER RESOURCE GUIDANCE STRATEGY IN DEVELOPMENT EFFORTS AT AL-WAHDAH TOJO UNA-UNA ISLAMIC ELEMENTARY SCHOOL - Suci Indasari (Adisam Publisher, 2025)
Educational institutions require professional human resources who can carry out their functions to achieve the goals that have been set because, in the world of education, humans play an important role in improving the quality of education. Educators are educators or teachers. The situation of teachers in Indonesia still needs special attention. Incompetent teachers are one of the causes of the low quality of education. One of the causes is the lack of selectivity in recruiting teachers, even the lack of understanding of the role of the position and the benefits of the recruitment. This study uses a qualitative method. Qualitative research with descriptive methods is used to study various events that occur in research subjects, aspects, symptoms, or conditions that arise from field findings. The results of the study indicate that the strategy for developing teaching resources including planning, organizing, leadership, supervision, purchasing, training, compensation, discipline, and dismissal strategies at SD IT Al- Wahdah Tojo Una-Una has been carried out well and by the regulations given in that place.